2013
DOI: 10.1371/journal.pgen.1003930
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair Genes Mlh1 and Mlh3 Modify CAG Instability in Huntington's Disease Mice: Genome-Wide and Candidate Approaches

Abstract: The Huntington's disease gene (HTT) CAG repeat mutation undergoes somatic expansion that correlates with pathogenesis. Modifiers of somatic expansion may therefore provide routes for therapies targeting the underlying mutation, an approach that is likely applicable to other trinucleotide repeat diseases. Huntington's disease HdhQ111 mice exhibit higher levels of somatic HTT CAG expansion on a C57BL/6 genetic background (B6.HdhQ111) than on a 129 background (129.HdhQ111). Linkage mapping in (B6x129).HdhQ111 F2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
211
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(228 citation statements)
references
References 96 publications
(186 reference statements)
17
211
0
Order By: Relevance
“…More recently, it was shown that short CAG/CTG slip-out structures were efficiently repaired by human MutL and MutS complexes [27,28], and to a lesser extent by MutS [27]. In mice in which Msh2, Msh3, Pms2, Mlh1 or Mlh3 were reduced or abolished, CAG/CTG repeat expansions were decreased [29][30][31][32][33][34][35][36][37]. This is also true when Msh2 was partially or totally depleted in a mouse model for fragile X premutation [38].…”
Section: Introductionmentioning
confidence: 96%
“…More recently, it was shown that short CAG/CTG slip-out structures were efficiently repaired by human MutL and MutS complexes [27,28], and to a lesser extent by MutS [27]. In mice in which Msh2, Msh3, Pms2, Mlh1 or Mlh3 were reduced or abolished, CAG/CTG repeat expansions were decreased [29][30][31][32][33][34][35][36][37]. This is also true when Msh2 was partially or totally depleted in a mouse model for fragile X premutation [38].…”
Section: Introductionmentioning
confidence: 96%
“…A second MutL homolog has been shown to act as an enhancer of CAG repeat expansions. Indeed, expansion-biased somatic mosaicism is reduced in Mlh3 heterozygous knockout mice and totally abolished in Mlh3 homozygous knockout mice suggesting that MLH3 is a limiting factor on the process of expansion as reported for MSH3 protein [69].…”
Section: Genetic Modifiers Of Somatic Mosaicismmentioning
confidence: 71%
“…It has been reported that Msh2 alleles delay the accumulation of mutant protein and destruction of mutant huntingtin in striatum and in specific neuron type from knock-in HdhQ111 mice [58,67]. Moreover, MLH1 also contributes to nuclear huntingtin and HD inclusion phenotypes [69]. Both data suggest that MSH2 and MLH1 may enhance the HD pathogenic process by modulating the somatic mosaicism in cooperation with MSH3 and MLH3 via the mismatch repair pathway.…”
Section: Are Genetic Modifiers a Therapeutic Target?mentioning
confidence: 97%
See 1 more Smart Citation
“…The loss of other MMR proteins such as PMS2 and MLHrelated endonucleases have also been found to suppress TNR expansions (195). MLH1, which is involved in all 3 mammalian MutL complexes, and MLH3 were found to be involved in somatic TNR expansions in HD mouse models (195,196). The protein PCNA acts as a BER cofactor to stimulate FEN1 cleavage and further interacts with all core BER proteins.…”
Section: Base Excision Repair In a Trinucleotide Repeat Hairpinmentioning
confidence: 99%